Organic leaching and metal removal with Sargassum filipendula - Veit, Márcia Teresinha; Gonçalves, Gilberto da Cunha; Fagundes-Klen, Marcia Regina; Silva, Edson Antonio da; Tavares, Celia Regina Granhen; Honorio, Jacqueline Ferandin (Acta Scientiarum. Technology, 2014)
The biosorption process with algae is usually carried out with a concomitant alginate leaching process. Alginate is identified as the main functional group, responsible for generating the most active sites. Biomass chemical and thermal pretreatment is an alternative process for reducing organic leaching. Experiments with different pH rates were performed to analyze the leaching process of pretreated (contact time: 24, 48 and 72 hours) and non-pretreated biomass of Sargassum filipendula. The concentrations of calcium, magnesium, sodium and potassium ions, as well as total organic carbon, were determined to evaluate the biomass sorption capacity. Capacities of native and pretreated biomass to remove the heavy metal ions Cr and/or Ni from solutions of different concentrations were compared. The ion competition effect on removal capacity was studied. The biosorbent had a higher affinity with chromium ion. Â